PERBAIKAN FASILITAS PEMINDAHAN BAG PAKAN UDANG DI DEPARTEMEN PACKAGING GUNA MENGURANGI RESIKO CEDERA TULANG BELAKANG - Rio Prasetyo Lukodono; Siti Kholisotul Ulfa (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2016)
Manual Materials Handling (MMH) activities still widely used in a job. This is because in this activity has a high flexibility, inexpensive, and easy to apply. However, these activities also constitute a risk when applied to the inadequate environment, less support of tool, and bad posture of work. Therefore, measurement of safety limit in doing the job by using a calculation based on the equation of NIOSH Lifting Index. The case study at PT. Central protein Prima Surabaya is the removal of shrimp feed bag that still use manual way. Acquisition of STRWL calculation results obtained for the removal of shrimp feed bag stacks 1, 2, 3, 4, 5, 6, and 7 from 5,003 Kg to 67,41 Kg. Actual load which worker must lifted in this case study on a pile of 1 to 7 is 25 kg. Load is lifted for the removal of shrimp feed bag bigger than STRWLmake it not feasible. CLI obtained in shrimp feed bag removal activity is 6.041 which value exceeds 3. Therefore CLI in this case study may create a risk of spinal cord injuries and to do their job changes. By measuring the changes in safety limits and do the work, expected reduced risk of injury to workers. After measuring the safe limit for the removal of bag obtained load is lifted workers have the risk of spinal injury, so it is given recommendations for improvement is by doing a redesign on a conveyor in the form of additional elevation (vertical) 57 cm at the end of the conveyor, as well as shortening the horizontal distance between the worker's body with a bag of shrimp feed time of transfer. With these recommendations obtained a decrease CLI becomes 1.795, which means that the risk of injury is between 1 <CLI ≤ 3 and can be reduced.